Survival Strategies Of UMKM In Bengkulu City In Facing Inflation (Phenomenological Study) - Yerni Puspita Sari; Ahmad Soleh; Kresnawati Kresnawati (Social Sciences Journal, 2026)
The purpose of this study was to determine the survival strategies of UMKM in Bengkulu City in facing inflation. This research method used descriptive qualitative and quantitative research, often referred to as mixed methods. A phenomenological study with SWOT analysis was used as qualitative research. Furthermore, the use of SWOT, EFE, IFE, IE, and QSPM matrices, all in numerical form, constitutes quantitative research. The research sample consisted of five UMKM operating as Padang restaurants in Bengkulu City. The data analysis technique used was descriptive qualitative and quantitative. The results of the study showed a total IFAS score of 2.73 and EFAS from the SWOT analysis of 3.10, placing the business position in Quadrant I (aggressive strategy) which means that the strategy is more emphasized on the strengths and opportunities that are owned, namely the quality of Minang's distinctive taste, customer loyalty, and strategic location of the business. The results of the QSPM (Quantitative Strategic Planning Matrix), the alternative strategy that is the main priority is the strategy chosen with the highest number of weight values, where the strategy is a market penetration strategy with a TAS (Total Attractive Score) value of 6.55 which means Expanding promotions through social media and digital platforms.